DEVELOPMENT OF HUMANISTIC PROFESSIONAL QUALITIES OF THE TEACHER IN THE PROCESS OF INTERACTIVE EDUCATION OF YOUNGER SCHOOL STUDENTS - Komar, Olha; Kilichenko, Oksana (Mountain School of Ukrainian Carpaty, 2023)
The article reveals the problem of developing the humanistic qualities of the teacher in the process of organizing interactive education in primary school. The professional and personal qualities which characterize a humane primary school teacher are defined. It is emphasized that special attention is paid to the organization of the educational process as effective multilateral communication. Applying one or another technology, in our case interactive, to solve the tasks of the educational process, the primary school teacher will definitely use appropriate teaching methods. That is, the implementation of training using certain technologies occurs primarily through a system of adequate methods, which are the core of this technology. The role of "active" and "passive" learning methods, when students act as the "object" of teachning, is analyzed. It is noted that interactive teaching methods provide the greatest space for self-realization of the student in learning and most closely correspond to a person-oriented approach. They are focused on the realization of the cognitive interests and needs of the individual, therefore special attention is paid to the organization of the process of effective multilateral communication, which is characterized by the absence of polarity and minimal concentration on the teacher's point of view. Participants of such communication are more mobile, open and active. Therefore, the key to understanding the role of interactive communication in the social development of a child, both a child and a teacher, is the thesis that a child's personality develops in unity, communication with the nearest micro-society, which includes peers and teachers. In addition, the use of interactive methods ensures the implementation of the idea of cooperation in the team, contributes to the improvement of the psychological climate in the classroom, and creates an atmosphere of goodwill during training. The study of the role of the organization of interactive learning in the development of humanistic qualities of primary school teachers was organized in the following directions: self-analysis of their personal and professional qualities and determination of the importance of interactive learning in the formation of humanistic qualities. It is noted that a special role in the development of the teacher's humanistic qualities in the process of organizing interactive learning is played by their readiness for professional activity